Spiritual diversity in social work practice the heart of helping - Canda, Edward R.; Furman, Leola Dyrud (Oxford University Press, 2020)
The first edition of this book (1999, Free Press) provided the first comprehensive framework of knowledge, values, and skills for addressing spiritual diversity in social work at a time when this topic was little known or accepted. The second edition (2010, Oxford University Press) was revised and expanded to reflect the significant growth of interest in spirituality within social work and other helping professions, in the USA and around the world. This third edition builds on that foundation and much expanded multidisciplinary and international work on the topic during the past eight years, including our own. In particular, this edition includes case examples and insights from a new third author, Hwi-Ja Canda, based on her 30 years of experience as a social work practitioner, in order to make the professional applications of our framework even more vivid and practical. The main new features of the third edition are: - Reorganization of content to enhance flow of ideas and guidelines for practice, including expansion of content on assessment and practice with two added chapters in Part III - Twice as many case examples and vignettes from personal and professional experiences, organized into 40 Scenarios throughout the book - Significantly expanded transdisciplinary literature review throughout the book - Increased integration of the strengths perspective throughout - Increase of international perspective, including analysis of worldwide professional codes of ethics - More exercises to engage the reader in personal and professional growth - Significant refinements of sections on human diversity, religious perspectives, and addition of 12 Steps perspective in Part II"--